(untitled) (Itinera, 2025)
This paper examines how AI-generated images reconfigure key aesthetic and epistemological categories within contemporary visual culture. Drawing on Nelson Goodman’s distinction between autographic and allographic art forms, we argue that AI image generation occupies a hybrid position, functioning as a “mixed case” where linguistic prompts serve as notational structures and generative outputs as autographic instantiations. Through the notion of semantic attractors, we describe how lexical inputs act as gravitational forces within the model’s latent space, guiding the emergence of visual and affective configurations. This dynamic is interpreted through conceptual blending theory, revealing how AI systems integrate heterogeneous domains into novel perceptual and semantic syntheses. Finally, we introduce the concept of the image-ideogram to analyze the cultural impact of deepfakes and synthetic imagery, suggesting that photorealistic synthesis now operates less as an epistemic index and more as a visual and linguistic resource within the accelerated economy of contemporary visual discourse.